Short-term effects of extended-release niacin on endothelial function in HIV-infected patients on stable antiretroviral therapy - Chow, Dominic C. (2010)
OBJECTIVE: To assess the short-term effects of extended-release niacin (ERN) on endothelial function in HIV-infected patients with low high-density lipoprotein-cholesterol (HDL-c) levels. METHODS: Randomized controlled study to determine the short-term effects of ERN on endothelial function, measured by flow-mediated vasodilation (FMD) of the brachial artery, in HIV-infected adults with low HDL-c. Participants on stable HAART with fasting HDL-c less than 40 mg/dl and low-density lipoprotein-cholesterol less than 130 mg/dl were randomized to ERN or control arms. ERN treatment started at 500 mg/night and titrated to 1500 mg/night for 12 weeks. Controls received the same follow-up but were not given ERN (no placebo). Participants were excluded if they had a history of cardiac disease, uncontrolled hypertension, diabetes mellitus, or were on lipid-low-ering medications such as statins and fibrates. Change in FMD was compared between arms with respect to baseline HDL-c. RESULTS: Nineteen participants were enrolled: 89% men, median age 50 years, 53% white/non-Hispanic, median CD4 cell count 493 cells/μl, and 95% of them had HIV RNA below 50 copies/ml. Participants receiving ERN had a median HDL-c (interquartile range) increase of 3.0 mg/dl (0.75 to 5.0) compared with −1.0 mg/dl in controls (−6.0 to 2.5), a P value is equal to 0.04. The median change in FMD was 0.91% (−2.95 to 2.21) for ERN and −0.48% (−2.65 to 0.98) for controls (P=0.67). However, end of study FMD for ERN was significantly different from controls after adjusting for baseline differences in FMD and HDL-c, 6.36% (95% confidence interval 4.85–7.87) and 2.73% (95% confidence interval 0.95–4.51) respectively, a P value is equal to 0.048. CONCLUSION: This pilot study demonstrated that short-term niacin therapy could improve endothelial function in HIV-infected patients with low HDL-c.